The impact of monetary policy on commercial bank lending in Malaysia: The investigation on agriculture, construction & manufacturing sectors - Mohd Harif, Mohd Amy Azhar; Abd Karim, Mohd Zaini; Abdul Adzis, Azira (2005)
The purpose of this dissertation is to investigate the impact of monetary policy on commercial bank lending in Malaysia from 1970-2000.This dissertation, is intended to answer two research questions: 1) Will a tightening of monetary policy in Malaysia affects commercial bank lending at the aggregate level? 2) Will a tightening of monetary policy in Malaysia affects commercial bank lending to agriculture, construction, and manufacturing sector? The objectives of this dissertation is to determine the impact of monetary policy tightening on commercial bank lending at aggregate level and sectoral level namely, agriculture, construction, and manufacturing loan.To achieve the objective, this dissertation employs the vector autoregression (VAR) technique.From the VAR analysis, the results suggested that a monetary policy tightening in Malaysia gives significant impact on commercial bank lending at both the aggregate level and sectoral level from 1970-2000.The results also suggest that a monetary policy tightening in Malaysia gives larger impact on agriculture loan during the period of 1970-1996, while during the period of 1970-2000 (including the period of financial crisis), a monetary policy tightening in Malaysia gives larger impact on construction loan.